Complete human CD1a deficiency on Langerhans cells due to a rare point mutation in the coding sequence. - Cerny, D; Thi Le, D; The, T; Zuest, R; Kg, S; Velumani, S; Khor, C; Mori, L; Simmons, C; Poidinger, M; Zolezzi, F; Ginhoux, F; et al. (Elsevier, 2016)
The family of CD1 molecules is structurally similar to MHC class I molecules, but the 2 protein families mediate fundamentally different immune functions. MHC class I molecules present peptides to T cells, whereas CD1 molecules present lipids to natural killer T cells and other CD1-restricted T cells.1 CD1a is highly expressed on human Langerhans cells (LCs), a specialized mononuclear phagocyte that is prevalent in the epithelial cell layer of the skin and mucosal surfaces. Epidermal LCs can function as classical antigen-presenting cells (APCs) to induce naive T-cell responses in draining lymph nodes, but also have a regulatory function in the skin via local induction of regulatory T cells and maintenance of epithelial barrier integrity.2,3 Human dermal dendritic cells (DCs) also express CD1a, but in much lower amounts compared with LCs. CD1a1 dermal DCs, which coexpress CD1c, have been shown to efficiently stimulate CD41 and CD81 T cells in vitro.4,5 However, immune deficiencies due to selective CD1a defects have not been previously described, and it has proved difficult to dissect the specific role of CD1a in immune regulation.